LAYANAN PROMOTIF BAGI BALITA BERISIKO STUNTING DI DESA CAMPLONG II, KECAMATAN FATULEU KABUPATEN KUPANG - ch, Christina Olly Lada; Lidia, Kartini; Soegianto, Sugi Deny Pranoto; Woda, ⁠Rahel Rara; Anggraini, Thalitha Ayu; Landutana, Umbu Djama; Hendrik, Einstein Daud Victor; Lulan, Alfa Julian; Tiran, Yessy Osinami; Waitau, Boymax Aprilio (Universitas Nusa Cendana, 2024)
The prevalence of stunted toddlers in Kupang district is still high, including in the partner area, namely Camplong-II village, Fatuleu sub-district. This village is one of the areas with sufficient water sources and adequate agricultural products, but a few stunted toddlers are still found. Adequate agricultural and livestock production does not guarantee that the nutritional status of toddlers will be good, even though sufficient food is available in the family, if the caregiver does not provide it according to the toddler's needs, the toddler will also experience malnutrition. Data from the Hamlet II Haumeni Posyandu, Camplong-II Village shows that there are 27 stunted toddlers (July 2022). The implementation of preventive promotive services for stunted toddlers or those at risk of stunting is intended as an effort to increase public knowledge about the prevention and handling of stunting. This activity aims to reduce stunting rates by providing counseling, cooking demonstrations, and distributing necessities. The output indicators are increasing knowledge about the prevention and handling of stunting and the use of food ingredients around for food menus. The expected output targets are increasing knowledge and skills of partners to serve nutritious food menus for toddlers and the availability of nutritious food ingredients for toddlers. The availability of protein and vegetable food sources is always needed by stunted toddler partners, so it is expected that two months after harvest, there will be an increase in the weight and height of stunted toddlers. Families who are intervened are expected to be a model for program duplication at other integrated health posts.